2013
DOI: 10.1111/ajt.12390
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis Transmission by Kidney Transplantation in Two Recipients From a Common Donor

Abstract: Strongyloides stercoralis hyperinfection in an immunocompromised host has a high mortality rate but may initially present with non-specific pulmonary and gastrointestinal symptoms. Donor-derived S. stercoralis by kidney transplantation is an uncommon diagnosis and difficult to prove. We report two renal allograft recipients on different immunosuppressive maintenance regimens that developed strongyloidiasis after transplantation from the same donor. Recipient 1 presented with a small bowel obstruction. Larvae w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
1
38
0
4
Order By: Relevance
“…This case adds to the existing reports of S. stercoralis transmission from donors to SOT recipients, [2][3][4][5] but there are some important differences in our case. All donor-to-recipient transmissions described so far were investigated when at least one SOT recipient presented with severe strongyloidiasis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This case adds to the existing reports of S. stercoralis transmission from donors to SOT recipients, [2][3][4][5] but there are some important differences in our case. All donor-to-recipient transmissions described so far were investigated when at least one SOT recipient presented with severe strongyloidiasis.…”
Section: Discussionsupporting
confidence: 54%
“…1 In recent years, some authors have reported the transmission of S. stercoralis from infected donors to recipients. [2][3][4][5] Interestingly, most cases were diagnosed when recipients presented with hyperinfection syndrome and donors were found to have S. stercoralis on retrospective testing.…”
Section: Introductionmentioning
confidence: 99%
“…La estrongiloidiasis ha sido reportada como la segunda causa de infección de origen parasitario en el paciente trasplantado renal, después de la toxoplasmosis, por lo que cada vez cobra más importancia el estudio especí-fico de este nematodo tanto en el donante como en el receptor (8,11). Es importante resaltar dos aspectos ; desde lo mejor de nuestro conocimiento este es el primer caso reportado en Colombia de hiperinfección por Strongyloides spp en un paciente trasplantado renal, por otro lado como se ha observado en otras publicaciones, identificar si la infección provenía del receptor o del donante es más complicado; en nuestro caso hay dos motivos que podrían indicar que la infección provenía del receptor y son que él siempre ha vivido en zona endémica y segundo que el receptor del otro riñón, no ha presentado ninguna sintomatología similar hasta el momento (11,12).…”
Section: Discussionunclassified
“…Es importante resaltar dos aspectos ; desde lo mejor de nuestro conocimiento este es el primer caso reportado en Colombia de hiperinfección por Strongyloides spp en un paciente trasplantado renal, por otro lado como se ha observado en otras publicaciones, identificar si la infección provenía del receptor o del donante es más complicado; en nuestro caso hay dos motivos que podrían indicar que la infección provenía del receptor y son que él siempre ha vivido en zona endémica y segundo que el receptor del otro riñón, no ha presentado ninguna sintomatología similar hasta el momento (11,12).…”
Section: Discussionunclassified
“…Even if there is only suspicion of an infection with Strongyloides stercoralis in a possible kidney donor, it is preferable to initiate the treatment with albendazole until the infection is eradicated. The same treatment can be administered to the transplant recipient [26,27]. It is worth noting that thiabendazole interferes in the liver with medications containing xanthine, but it does not interefere in its hepatic metabolism with the calcineurin inhibitors.…”
Section: Parasitic Infectionsmentioning
confidence: 99%